2017
DOI: 10.3747/co.24.3588
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma Ex Pleomorphic Adenoma: Case Report and Options for Systemic Therapy

Abstract: The most common benign salivary tumour is a pleomorphic adenoma. Transformation to malignancy, carcinoma ex pleomorphic adenoma (cxpa), occurs in 6% of cases. Management focuses on surgical resection and radiotherapy; however, rare cases require systemic management. We present the case of a 60-year-old woman with a cxpa of the left parotid gland who required systemic therapy for locally recurrent disease. Treatment options were guided by the literature concerning malignant salivary gland tumour and by whole-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
1
Order By: Relevance
“…In 2009, Lüers JC et al13 retrospectively analyzed 22 patients with CXPA of the parotid gland and showed that patients receiving chemotherapy even had a lower 5-year overall survival rate (50%) than those receiving no chemotherapy (63%). However, in a case report of CXPA from a Canadian group, chemotherapy with CAP (cyclophosphamide, doxorubicin, and cisplatin) result in an excellent clinical and radiologic response 14. Therefore, the role of chemotherapy in CXPA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Lüers JC et al13 retrospectively analyzed 22 patients with CXPA of the parotid gland and showed that patients receiving chemotherapy even had a lower 5-year overall survival rate (50%) than those receiving no chemotherapy (63%). However, in a case report of CXPA from a Canadian group, chemotherapy with CAP (cyclophosphamide, doxorubicin, and cisplatin) result in an excellent clinical and radiologic response 14. Therefore, the role of chemotherapy in CXPA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CXPA is unknown. Chooback et al[5] proposed a role for the deficiency of some genes, such as those on chromosomal arms 8q, 12q, and 17p. Kim et al[6] suggested that the accumulation of genetic instabilities was the main cause of malignant transformation in pleomorphic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiation is typically reserved for patients with stage III/IV disease 99 . At present, there is no well-defined role for systemic therapy 99,100 . It should be noted that the distinction between de novo and ex-PA malignancies is not merely semantic.…”
Section: Myoepithelial-rich Pleomorphic Adenoma and Myoepithelial Car...mentioning
confidence: 99%